The Effect of Acceptability of Dadih-based Functional Bread on Food Intake and Weight Gain of Pregnant Women in Padang City - Helmizar, Helmizar; Juliyarsi, Indri; Fadri, Rince Alfia; Yusrawati, Yusrawati (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The aim of this study was to analyze the acceptability of dadih-based functional bread and its effect on food intake and weight gain pregnant women. The study design was a quasi-experimental randomized controlled trial involving 88 pregnant women who were given bread (50 g) and filled with dadih-based vla (30 g) six times a week for three months. Acceptability was assessed using the Comstock method and food intake was assessed using the 2x24-hour recall method. Data were analyzed using chi-squared and independent t-tests. There is a relationship between the acceptability of bread with dadih vla and food intake (p<0.005). The results showed a significant difference in weight gain (p<0.005) between the control and intervention groups that was provided with the dadih-based vla, a typical Dutch dessert sauce. Dadih contains high calories, fat, and protein, which could help increase maternal weight. Respondent who consumed bread with dadih vla were able to meet the nutritional needs adequately.